1983
DOI: 10.1577/1548-8659(1983)112<293:dolfrt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Larval Fishes Related to Potential Navigation Impacts on the Upper Mississippi River, Pool 7

Abstract: Ichthyoplankton samples were collected twice monthly during spring and summer 1981 from a variety of habitats in Navigation Pool 7 of the upper Mississippi River. Larval-fish distributions in the pool and variations in those distributions were analyzed relative to potential impacts of increased commercial navigation. Although as many as 66 species of adults have been found in the area (33 considered common), only 17 taxa were identified from our collections. In April and May, most larvae were collected in main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0
4

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 0 publications
8
34
0
4
Order By: Relevance
“…Larval crappie were 3 16% more abundant in nighttime samples than day samples. Other studies have found similar results regarding larval crappie collections (Lewis and Siler 1980, Holland and Sylvester 1983, Sarnmons and Bettoli 1998. Multiple factors may contribute to the differences between daytime and nighttime collections including larval diel migrations, net avoidance, age of larvae, and changing reservoir conditions.…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…Larval crappie were 3 16% more abundant in nighttime samples than day samples. Other studies have found similar results regarding larval crappie collections (Lewis and Siler 1980, Holland and Sylvester 1983, Sarnmons and Bettoli 1998. Multiple factors may contribute to the differences between daytime and nighttime collections including larval diel migrations, net avoidance, age of larvae, and changing reservoir conditions.…”
Section: Methodssupporting
confidence: 71%
“…The desire to assess crappie year-class strength earlier has led managers to sample larval populations (Taber 1969, Tuberville 1979, Cada et al 1980, Lewis and Siler 1980, Van Den Avyle and Fox 1980, Holland and Sylvester 1983, Thayer et al 1983, Muth and Schrnulbach 1984, Claramunt et al 2005. McDonaugh and Buchanan (1991) documented a high correlation between age-0 and age-1 crappie densities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protolarvae are common in the drift in spring (Fig. 2) when water temperatures are 14 "C to 16 "C. A strong die1 pattern of drift is evident for this taxa (Holland & Sylvester, 1983). Movement of larvae from backwaters to the main channel peaks at dusk.…”
Section: Habitat Variationsmentioning
confidence: 92%
“…Ce rôle de nurserie est confirmé par l'entrée d'adultes en phase de maturation et formant un troisième groupe au printemps. La remontée d'adultes dans les bras morts durant cette période de hautes eaux printanières assure donc, d'une part, le recrutement qui maintient un peuplement important et diversifié entre le bras mort et la Garonne (Daget in Welcomme 1979, Van Vooren 1981, Holland & Sylvester 1983, Scott & Nielsen 1989 et, d'autre part, le déroulement des processus biologiques de reproduction des poissons (Carrel 1986, Sheaffer & Nickum 1986, Copp 1989.…”
Section: Gaiunclassified